Stratton Hall's Christmas Party, Judy Sutton (with headband), Suzanne Gould, J1968, Rene Bejosa, Mareen McGonigle, Alice Beake (with nightcap), Leslie Bell Wharton, J1968, Judith Breakstone, J1968, December 1964 - Unknown (Tufts Archival Research Center, 2005)
5x7